The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.17645/si.v8i3.2755
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Contested Notion of Social Inclusion and Gender Inclusivity within eSport Spaces

Abstract: With an emphasis on virtual engagement, creativity, and diverse competitive platforms, eSport is being explored as a new activity to achieve development outcomes within the Sport for Development (SfD) movement (Kidd, 2008). Research has shown the potential of eSport to provide opportunities for social interaction, bonding, and building social capital (Trepte, Reinecke, & Juechems, 2012). This exploratory research, conducted in 2019, examines the current eSport landscape and utility of eSport as a space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 33 publications
0
30
0
1
Order By: Relevance
“…Emily Jane Hayday and Holly Collison explore the role of esport as a new sport-based activity to achieve the developmental goals of the sport for development (and peace) movement (Hayday & Collison, 2020). Using focus groups and interviews with game publishers, sport for development organizations, esports teams, tournament organizers, and gamers, the authors question the utility of esports as a space to enact social inclusion for women and girls.…”
Section: Spaces and Placesmentioning
confidence: 99%
See 2 more Smart Citations
“…Emily Jane Hayday and Holly Collison explore the role of esport as a new sport-based activity to achieve the developmental goals of the sport for development (and peace) movement (Hayday & Collison, 2020). Using focus groups and interviews with game publishers, sport for development organizations, esports teams, tournament organizers, and gamers, the authors question the utility of esports as a space to enact social inclusion for women and girls.…”
Section: Spaces and Placesmentioning
confidence: 99%
“…Using focus groups and interviews with game publishers, sport for development organizations, esports teams, tournament organizers, and gamers, the authors question the utility of esports as a space to enact social inclusion for women and girls. As an analytical transdisciplinary framework to understand gender dynamics, Hayday and Collison (2020) innovatively combine Lefebvre's spatial theory and Bailey's conceptual model of social inclusion. Findings showed that the dominant hypermasculine dynamics of digital platforms contribute to gender inequality and discrimination (e.g., sexism) within such online communities.…”
Section: Spaces and Placesmentioning
confidence: 99%
See 1 more Smart Citation
“…Esports is embraced in sport management academics (Jang and Byon, 2020a; Pizzo et al , 2018). Each game’s genre (Hamari and Sjöblom, 2017; Jang and Byon, 2020b; Lucas and Sherry, 2004) and gender (Hayday and Collison, 2020; Jang and Byon, in press; Vermeulen et al , 2017) have revealed the significant role of moderators between gameplay intention and its drivers from separated studies previously. In other words, according to genre or gender, the consumers showed differences in their behavioral intentions and factors that lead to the consumption.…”
mentioning
confidence: 91%
“…Regarding gender, Hayday and Collison (2020) stated the toxicity in gender inequality in the gamer cultures. Vermeulen et al (2017) indicated the relationship between women’s social interaction and gamer identity.…”
mentioning
confidence: 99%